Peran Mahasiswa KKN-T dalam Pengembangan Desa Wisata Di Desa Losari, Kec. Gondang, Kab. Nganjuk. - Jawelery Wahyu Ninda Ariesta; Berliana Cherry Alma Naila; Siti Syarifatul Laily Suhri; Muhammad Rizky Awwalul Ramadhan; Ivan Christopher Sukandar (CV. Aksara Global Akademia, 2023)
Thematic Real Work Activities (KKN-T) with a tourism village scheme aim to explore, develop and promote Losari Village tourism to make it a tourism village. The method used in community service activities is a qualitative descriptive method because it describes the phenomena that occur in depth, and describes the responses without testing the hypothesis. Data collection was taken through interview sessions with village officials, the community and other village organizations. Furthermore, the planning stage is carried out, namely a field survey as a tourism potential multiplier. secondly the implementation of a work program to answer challenges regarding the development of a tourist village in Losari Village. Work programs in the form of outreach, revitalization, Appropriate Technology, and Event Bazaar. In the final stage, namely evaluation as a stage of monitoring the development of a tourist village.